Manganese-Catalyzed Direct Olefination via an Acceptorless Dehydrogenative Coupling of Methyl Heteroarenes with Primary Alcohols - Barman, Milan K.; Waiba, Satyadeep; Maji, Biplab (Synlett, 2019)
Synthesis of olefins utilizing different catalytic strategies is an emerging topic in organic chemistry. However, despite of tremendous progress in the field the direct olefination of C(sp3)–H bonds using primary alcohols via an acceptorless dehydrogenative coupling (ADC) is not developed. Such an ADC reaction is highly environmentally benign as it produces dihydrogen and water as the sole byproducts. The liberated dihydrogen can potentially be used as an energy source. In this Synpact article, we present the recent development of ADC reaction as a tool to make unsaturated molecules and a summary of our recently developed synthetic procedure for the preparation of olefins employing an ADC reaction of methyl heteroarenes with alcohols. The catalyst development using an earth’s abundant metal manganese and the scope of such reaction is discussed.1 Introduction2 The Acceptorless Dehydrogenative Coupling as a Tool to Make Unsaturated Molecules3 Transition-Metal-Catalyzed Coupling of Alcohols with Methyl-Substituted Heteroarenes4 Development of the Manganese Catalyst for the Olefination of Methyl-Substituted Heteroarenes5 Scope and Limitation of the Manganese-Catalyzed Direct Olefination of Methyl-Substituted Heteroarenes6 Mechanistic Studies and Proposed Mechanism7 Conclusion
Keywords: manganese; acceptorless dehydrogenative coupling; NNN pincer ligand; olefination; methyl heteroarenes